Critical Ecospirituality and Ecclesial Subsidiarity A Reflection on Sean McDonagh’s Environmental Theology for Agrarian Justice in Sekadau, West Kalimantan - Dismas Kwirinus; Alphonsus Tjatur Raharso; Ignatius Dendi (Jayapangus Press, 2026)
This study seeks to develop a theological understanding of Rimba Kobar’s critical ecospirituality as a contextual faith praxis that promotes agrarian justice in Sekadau, West Kalimantan, in the light of Sean McDonagh’s environmental theology. Employing a qualitative-reflective theological approach, the research explores the ecological spirituality of local communities and connects it with the principle of subsidiarity in Catholic Canon Law. The findings indicate that Rimba Kobar’s ecospirituality represents not only an ecological expression but also a form of moral resistance against agrarian structural injustice, resonating with the spirit of subsidiarity affirming the autonomy and dignity of grassroots communities in caring for creation. The integration of critical ecospirituality and subsidiarity paves the way for a contextual and participatory reconstruction of Catholic environmental theology, one that stands in solidarity with local communities. Thus, this study highlights the necessity of synergy between ecological theology, local spirituality, and Church law in realizing socio-ecological justice within Indonesia’s agrarian landscape.